Comparison between FRAIL Scale and Clinical Frailty Scale in predicting hospitalization in hemodialysis patients - Barbosa, Elisabete Mouzinho Soares [UNESP]; Pereira, Amanda Gomes [UNESP]; Mori, Vitória [UNESP]; da Silva Neves, Renan [UNESP]; Vieira, Nayane Maria [UNESP]; Silva, Maryanne Zilli Canedo [UNESP]; Seki, Marcos Mitsuo [UNESP]; Rodrigues, Hellen Christina Neves; Costa, Nara Aline; Ponce, Daniela [UNESP]; Balbi, André Luís [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; et al. (Oxford University Press (OUP), 2023)
Background: To assess the prevalence of frailty by the Clinical Frailty Scale (CFS) and the 5-item FRAIL scale and their association with hospitalization in hemodialysis (HD) patients. Methods: This was a prospective observational study. We included patients of both genders ≥ 18 years old in HD treatment for at least 3 months. Demographic, clinical, and routine laboratory data were retrieved from the medical charts. Two different frailty assessment tools were used, the CFS and the FRAIL scale. Participants were followed up for 9 months and hospitalizations for all causes were evaluated. A Venn diagram was constructed to show the overlap of possible frailty and pre-frailty. Cox regression was used to identify the association between frailty and hospitalization. The significance level was 5%. Results: A total of 137 subjects were included in the analysis. The median age was 61 (52–67) years and 60% were male. The hospitalization rate and mortality in 9 months were 22.6% and 7.29%, respectively. Regarding frailty, the overall prevalence was 13.8% assessed by CFS and 36.5% according to the FRAIL scale. In the Cox regression, frailty by FRAIL scale was associated with a 2.8-fold increase in the risk of hospitalization (OR = 2.880; 95% CI = 1.361–6.096; p = 0.006), but frailty assessed by the CFS was not associated with the need for hospitalization. Conclusion: In HD patients, the FRAIL scale proved to be an easy-to-apply tool, identifying a high prevalence of frailty and being a predictor of hospital admission. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Frailty; Hemodialysis; Hospitalization; Scales